Sistem Informasi Pendaftaran dan Verifikasi Isbat Nikah pada Kantor Urusan Agama Kecamatan Limboro Berbasis Web - Muspirah Muspirah; Sapriadi Sapriadi; Zulkifli Said; Basri Basri (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2026)
Marriage confirmation services are often hampered by manual procedures, leading to delays and administrative errors. This study aims to design and implement a web-based Marriage Confirmation Information System to facilitate registration, document uploads, and online monitoring of verification status and court schedules. The system was developed using the PHP programming language and MySQL database using the Waterfall method, encompassing analysis, design, implementation, and testing. The results show that the system is capable of optimally performing all managerial functions, from document validation to report automation. Black Box testing confirmed that all features functioned as expected and were easy to use. In addition to improving bureaucratic efficiency, the system ensures data security through login encryption and provides transparency through real-time status tracking. The presence of this platform significantly saves time and transportation costs for the public, as bureaucratic processes can be monitored from anywhere. In conclusion, this system successfully supports the digitalization of public services and improves the quality of administration within the Office of Religious Affairs (KUA) and Religious Courts, thereby realizing more effective, efficient, accountable, and modern governance for all levels of society